Effective Virtual Environments (International Journal of Engineering and Computer Science, 2021)
Abstract—Since the power of technology is in a state of continuous growth, many organisations are adopting the use of a virtual environment. There is no doubt that COVID-19 has played a significant role in accelerating and spreading the adoption of such a trend in different sectors, such as education, sales, software development, and medical sectors. Although the increasing trend may be towards building virtual teams, there are still some aspects not ideally handled by virtual environments. This paper presents the challenges and barriers, where current technologies used in establishing virtual environments have not yet been covered. In addition, it provides guidelines that can be used in designing and building software tools that support collaboration in virtual environments.